2015
DOI: 10.1016/j.msard.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of multiple sclerosis relapse: The NARCOMS participant perspective

Abstract: Acute relapses continue to be a significant aspect of multiple sclerosis (MS) on both the epidemiologic level and the individual patient level. Past work demonstrates residual disability from relapses as well as high patient-reported rates of ineffective relapse treatment. To better characterize the impact of MS relapses on the patient, a relapse-specific survey was administered through the North American Research Committee on Multiple Sclerosis (NARCOMS) Registry to 1000 registry participants who had reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…To better understand the status of patient care, the Myasthenia Gravis Foundation of America (MGFA) established a patient registry in collaboration with the University of Alabama at Birmingham, starting in 2013. The MG Patient Registry (MGR) is modeled after the North American Research Committee on Multiple Sclerosis Registry (NARCOMS) and includes voluntarily provided information from patients obtained through questionnaires addressing basic demographics, diagnosis, treatment, and insurance status . The data obtained also included validated MG‐specific disease severity scales: the MG—Activities of Daily Living (MG‐ADL) and the 15‐item MG Quality of Life‐15 (MG‐QOL15) instruments .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the status of patient care, the Myasthenia Gravis Foundation of America (MGFA) established a patient registry in collaboration with the University of Alabama at Birmingham, starting in 2013. The MG Patient Registry (MGR) is modeled after the North American Research Committee on Multiple Sclerosis Registry (NARCOMS) and includes voluntarily provided information from patients obtained through questionnaires addressing basic demographics, diagnosis, treatment, and insurance status . The data obtained also included validated MG‐specific disease severity scales: the MG—Activities of Daily Living (MG‐ADL) and the 15‐item MG Quality of Life‐15 (MG‐QOL15) instruments .…”
Section: Introductionmentioning
confidence: 99%
“…The MG Patient Registry (MGR) is modeled after the North American Research Committee on Multiple Sclerosis Registry (NARCOMS) and includes voluntarily provided information from patients obtained through questionnaires addressing basic demographics, diagnosis, treatment, and insurance status. 7 The data obtained also included validated MG-specific disease severity scales: the MG-Activities of Daily Living (MG-ADL) and the 15-item MG Quality of Life-15 (MG-QOL15) instruments. [8][9][10][11][12] The MGR has previously identified differential gender effects of MG and its treatment in quality of life and assessment of adverse effects to prednisone treatment.…”
mentioning
confidence: 99%
“…It was followed by leg-foot weakness (63%), numbness-tingling (55%), difficulty in walking (51%), hand-arm weakness (49%), coordination difficulties (47%), dizziness-balance (46%), muscle tightness-stiffness (46%), cognition (thinking-memory) problems (42%), vision problems (34%), bladder problems (31%), painburning-itching (27%), bowel problems (19%), speech changes (16%), chewing-swallowing problems (14%), and sexual problems (8.5%) (33). Visual, sensory, and brainstem relapses were found more frequently in early disease and in younger patients.…”
mentioning
confidence: 99%
“…More than half of patients (55.2%) stated that their school or work lives were impacted and it was shown that this duration was 12.7 days on average (33).…”
mentioning
confidence: 99%
“…30 Among MS patients from NARCOMS registered 17% indicated serious adverse effects after a long-period of GCs treatment, the majority completed treatment; only 0.8% stopped therapy because of adverse effects. 31 In our study nobody was refused the GCs therapy.…”
Section: Control Of Gcs Side Effects Occurrence In Ms Patientsmentioning
confidence: 55%